Coding enhanced joint detection for multiple access communications - Learned, R.; Singer, A.C. (Proceedings of the 1998 IEEE International Conference on Acoustics, Speech and Signal Processing, ICASSP '98 (Cat. No.98CH36181), 1998)
A low complexity approach to coding-enhanced multi-user detection is developed to mitigate the problems associated with the near-far effect and to permit a more efficient assignment of channel resources relative to current multiple access (MA) communications systems. Through prudent integration of error correction decoding, multi-user and inter-symbol interference equalization and stripping, a low complexity near-far resistant multi-user joint detector/decoder has been developed which exhibits significant performance gains relative to the best known low complexity joint detection/decoding procedures reported in literature. Empirical analysis of the coding-enhanced multi-user detector (CMD) for a case of heavy intersymbol interference and multi-user interference shows a 3 dB improvement over these best known methods.